Odpowiedzi

2010-01-20T14:56:12+01:00
{2x+y=9
{5x-4y=3

y = 9-2x
5x-4(9-2x)=3
5x-36+8x=3
13x=39 / :13
x = 3

y = 9-2*3
y = 9-6
y = 3


{3x-2y=5
{2x-y=4 / *(-2)

3x-2y=5
-4x+2y=-4 / +
-x = 1
x = -1

2*(-1) - y = 4
-2-y = 4
-y = 6
y = -6


{4x-5y=-4
{-2x+3y=1,1 / *2

4x-5y=-4
-4x+6y=2,2 / +
y = -1,8

-2x+3*(-1,8)=1,1
-2x-5,4=1,1
-2x = 6,5 / :(-2)
x = -3,25


{-2x+y=0
{3x-3y=1

y = 2x
3x-3*2x=1
3x-6x=1
-3x=1 / :(-3)
x = - 1/3

y = -2/3


{y+2-(3-x)=0
{x-2=5-(2-y)

y+2-3+x=0
x-2=5-2+y

y+x = 1
x-y=5 / +
2x = 6 / :2
x = 3

y = 1-x
y = -2
1 1 1
2010-01-20T15:07:00+01:00
A)
2x+y=9|*4
5x-4y=3

8x+4y=36
5x-4y=3
13x=39
x=3

2*3+y=9
y=9-6
y=3

b)
3x-2y=5
2x-y=4|*(-2)

3x-2y=5
-2x+2y=-8
x=-3

3*(-3)-2y=5
-2y=14
y=-7

c)
4x-5y=-4|*3
-2x+3y=1,1|*5

12x-15y=-12
-10x+15y=5,5
2x=-6,5
x=-3,25

4*(-3,25)-5y=-4
-5y=9
y=-1,8

d)
-2x+y=0|*3
3x-3y=1

-6x+3y=0
3x-3y=1
-3x=1
x=-1/3

-2*(-1/3)+y=0
y=-2/3

e)
y+2-(3-x)=0|*2
x-2=5-(2-y)|*2

2y+4-6-2x=0
2x-4=10-4-2y

-2x+2y=2|:2
2x+2y=10

-x+y=1
2x+2y=10

y=1+x
2x+2(1+x)=10
2x+2+2x=10
4x=8
x=2

y=1+2
y=3


1 5 1